Rawabogo Community's Attention in Developing of Tourism Village (Study Case: Rawabogo Village, Ciwidey District) - Indratno, Imam; Chamid, Chusarini; Judiantono, Tonny; Sonya, Vermanda Maharani; Yuniar, Nurrhisma (KnE Social Sciences, 2023)
Rawabogo Village is one of the villages in Ciwidey District which is unique with its historical site of Mount Nagra Padang and indigenous peoples. In the development of the Rawabogo Tourism Village, there were problems concerning community participation and empowerment. Community participation is built through an understanding of the desires, interests, demands, and a sense of ownership of the to develop tourism village. However, the measurement process related to desires, interests, demands, and a sense of ownership is difficult to measure accurately and dynamically using questionnaires and interviews. So it is necessary to have other measurement methods that can support the results of the questionnaires and interviews. Thus, this study aims to identify the attention of the people of Rawabogo Village to the development of tourism villages. The type of research is mixed research and data collection method used in this research comprises the primary and secondary data, while the sampling method used is purposive sampling with 10 respondents. The analysis result shows that the Rawabogo communities have high attention in developing the Rawabogo Tourism Village, which is also supported by obtaining the Saccadic movement pattern and fixation on each respondent, as well as the number of blinks which as a whole represent the average number of blinks of adults. The application of this mixed method, the eye tracking method and the classical method (questionaries and interviews), is the first step to including the scientific measurement of public awareness in the planning or development process. Keywords: Attention, Community, Tourist Village